Highly selective α-aryloxyalkyl C–H functionalisation of aryl alkyl ethers. Issue 43 (28th October 2022) - Bell, Jonathan D.; Robb, Iain; Murphy, John A.
Abstract : We report highly selective photocatalytic functionalisations of alkyl groups in aryl alkyl ethers with a range of electron-poor alkenes using an acridinium catalyst with a phosphate base and irradiation with visible light (456 nm or 390 nm). Abstract : We report highly selective photocatalytic functionalisations of alkyl groups in aryl alkyl ethers with a range of electron-poor alkenes using an acridinium catalyst with a phosphate base and irradiation with visible light (456 nm or 390 nm). Experiments indicate that the reaction operates via direct single-electron oxidation of the arene substrate ArOCHRR′ to its radical cation by the excited state organic photocatalyst; this is followed by deprotonation of the ArOC–H in the radical cation to yield the radical ArOC˙RR′. This radical then attacks the electrophile to form an intermediate alkyl radical that is reduced to complete the photocatalytic cycle. The oxidation step is selective for activated arenes (ArOR) over their non-activated counterparts and the subsequent deprotonation of the methoxy group affords the α-aryloxyalkyl radical that leads to a wide range of functionalised products in good to excellent yield.